Pruning inflorescences reduces the yield of neutral-day strawberry cultivars - Anzolin, Jefferson; Grando, Luiza Alessandra; Albrecht, Gustavo Eduardo; Fante, Rudinei; Trentin, Thomas dos Santos; Turmina, Ana Paula Fernandes de Lima; Antunes, Luis Eduardo Corrêa; Chiomento, José Luís Trevizan (Comunicata Scientiae, 2024)
The lack of information on inflorescence pruning of strawberry cultivars can compromise fruit yield and quality. The aim of this study was to investigate whether inflorescence pruning intensities interfere with the horticultural potential of strawberry cultivars. The treatments studied were three cultivars (‘Albion’, ‘Monterey’, and ‘San Andreas’) and four inflorescence pruning intensities (no pruning, removal of the first inflorescence, removal of the first two inflorescences, and removal of the first three inflorescences). The experiment was laid out in randomized blocks, with four replications. Fruit production and quality were assessed. ‘Monterey’ produced the most fruit and had the highest total strawberry production. Regardless of the cultivar, the total number of fruits and the total yield decreased linearly as the intensity of inflorescence pruning increased. In conclusion, increasing the intensity of inflorescence pruning reduces the productive potential of strawberry plants. Regardless of pruning, ‘Monterey’ has the best productive performance. The chemical quality of strawberries is not influenced by the pruning and cultivars studied.